AICCRA capacity building on Climate-Smart Agriculture Investment Planning equips Kenyan national and sub-national stakeholders to implement climate action. - Jalango, Dorcas; Kinyua, Ivy; Mogaka, Bwema; Akoko, Tessie; Karanja, Regina (2024)
The AICCRA Kenya project conducted four capacity-building workshops for national and sub-national stakeholders using the Kenya Climate-Smart Agriculture Investment Plan (KCSAIP) [5] to provide stakeholders with hands-on training on inclusive and participatory CSA investment planning to access climate finance. In turn, the trained stakeholders trained 4 community groups, Climate Change Committee members in 5 wards, 11 Agricultural Sector Development Support Programme (ASDSP) officers, and developed 8 bankable1 proposals to access climate-change grants.